Effect of three non-protein thiols on CHO cells exposed to low doses of X-radiation - de Luca, Julio Cesar (2013)
The goals of this study were to determine whether cysteamine, β-mercaptohetanol and glutathione protect CHO K1 cells against chromosomal aberrations induced by low doses of X-radiation, as well as whether radiation protection is related to physical properties of those thiols. Experimental design included four different treatments: (a) control, (b) cells treated with 5 mM of each thiol, (c) cells treated with 100 mGy of X-rays and (4) cells treated with 5 mM of each thiol and 100 mGy X-rays. In combined treatment, all thiols were added 30 min before irradiation. Thiols remained until cell sacrifice (18 h). Maximum protection was afforded by cysteamine, the minimum protection was produced by glutathione while β-mercaptohetanol did not sow radioprotection effect. These results are consistent with the electrical charges and chemical structure of the three thiols and might be explained by the lower or higher access to DNA.